2021
DOI: 10.1115/1.4051129
|View full text |Cite
|
Sign up to set email alerts
|

New Correlations for Flow and Conjugate Heat Transfer With Surface Radiation Characteristics of a Real-Scale Infrared Suppression System With Conical Funnels

Abstract: The consistent and accurate prediction of fluid flow and heat transfer characteristics in an infrared suppression (IRS) device is challenging due to the complex nature of the flow features. The cool ambient air intake and subsequent mixing of hot exhaust gas from the engine in the cargo/naval ships are done inside the IRS system. The objective is to propose correlations for mass entrainment and outlet temperature of IRS device with conical funnels stacked one above the other. The mass intake rate and funnel ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The radiation heat transfer equation for scattering, absorbing, and emitting, medium at some location r in the direction of s as given by Chandrakar et al, 26 Mukherjee et al, 27 and Saedodin 40 is calculated by dI(r,s)italicds+(a+σs)I(r,s)=an2σT2π+σs4π04πI(r,sfalse′)(s,s)dθtrue′,where the absorption coefficient is denoted by a , the refractive index is denoted by n , the radiation intensity is denoted by I , the scattering coefficient is denoted by σs the phase function is denoted by ϕ, and the solid angle by θ.…”
Section: Numerical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The radiation heat transfer equation for scattering, absorbing, and emitting, medium at some location r in the direction of s as given by Chandrakar et al, 26 Mukherjee et al, 27 and Saedodin 40 is calculated by dI(r,s)italicds+(a+σs)I(r,s)=an2σT2π+σs4π04πI(r,sfalse′)(s,s)dθtrue′,where the absorption coefficient is denoted by a , the refractive index is denoted by n , the radiation intensity is denoted by I , the scattering coefficient is denoted by σs the phase function is denoted by ϕ, and the solid angle by θ.…”
Section: Numerical Approachmentioning
confidence: 99%
“…The radiation heat transfer equation for scattering, absorbing, and emitting, medium at some location r in the direction of s as given by Chandrakar et al, 26 Mukherjee et al, 27…”
Section: Radiation Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohanty et al [12] investigated the flow field of IRS suppression device with a conical funnel and found that cylindrical funnels have higher air entrainment coefficient than conical funnels. Mukherjee et al [13] proposed a correlation between the mass inlet ratio and temperature ratio of outlet by investigating the geometric parameters of the Infrared Suppression System. Chandrakar et al [14] researched the comprehensive effect of free convection and surface radiation in infrared suppression devices and showed that surface radiation can influence the convection characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Unsteady mixed forced-buoyancy convection through channel with a forward facing step by addressing the mirror in a duct undergoing sudden expansion was presented by Inam and Lappa (2022). Fluid flow and heat transfer characteristics in infrared suppression (IRS) device, which is complex nature of the flow features, were discussed by Mukharjee et al (2021). They have taken cool ambient air by mixing of hot exhaust gas from the engine in the cargo/naval ships are done inside the IRS system as working fluid.…”
Section: Introductionmentioning
confidence: 99%